A experiência macro-oikoumene em tempos incertos: desafios e utopias - Nascimento, Claudemiro Godoy do (Revista eclesiástica brasileira, 2005)
This article intends to discuss ecumenism in the various sectors of civil and political society (Gramsci, 1985 and Gohn, 2001). We begin by examining the origin of the ecumenical and macro-ecumenical movements and in a next stage, seek a theoretical basis for our discussion through a careful reading of the Johannine writings, having as background the Gospel message. Finally, we will show how a macro-ecumenical experience can occur, using as example two concrete realities: the first experienced by the Little Sisters and the Little Brothers of Jesus, that have Brother Charles de Foucauld’s spirituality and the second, by the Brothers from the Taizé Community.